The Association of Pulmonary Flow Characteristics With Cardiac Function in Tricuspid Valve Malformation Fetuses: Study With Two‐Dimensional Speckle Tracking Echocardiography. (2nd November 2021) - Liu, Juanjuan; Cao, Haiyan; Cui, Li; Zhang, Yi; Song, Xiaoyan; Ma, Jing; Shi, Jiawei; Zhang, Li; Hong, Liu; Xie, Mingxing
Abstract : Objectives: To explore the relationship between cardiac function and pulmonary flow characteristics in tricuspid valve malformation (TVM) fetuses by conventional and speckle tracking echocardiography. Methods: Eighty‐eight TVM fetuses were retrospectively included and compared with 80 normal controls. TVM fetuses in each trimester were divided into two subgroups according to pulmonary flow characteristics: those with normal pulmonary flow (TVM‐N) and those with reduced or absent pulmonary flow (TVM‐R/A). Cardiac measurements, Celermajer index, and Simpson‐Andrews‐Sharland (SAS) score were obtained. Speckle tracking echocardiography was used to compute ventricular deformation parameters. Results: TVM fetuses demonstrated significantly lower global longitudinal strain (GLS) and strain rate for both ventricles than controls (all P < .05). When compared with TVM‐N, left ventricular (LV) ejection fraction, LV fractional area change, right ventricular (RV) fractional area change, LVGLS, and RVGLS were significantly reduced (all P < .05), while the RV diameter Z‐score, RV/LV diameter, SAS score, and Celermajer index were obviously increased in TVM‐R/A in both trimesters (all P < .05). Both LVGLS and RVGLS correlated with cardiothoracic circumference ratio, RV diameter Z‐score, RV/LV diameter, Celermajer index, and SAS score (all P < .01). There was a slow decline for LVGLS and RVGLS in TVM‐N fetuses throughout the gestation. Conversely, these two parameters worsened rapidly in TVM‐R/A group. Conclusions: TVM fetuses present biventricular dysfunction by deformation analysis in the second and third trimester of pregnancy. TVM fetuses with reduced or absent pulmonary flow exhibit significantly greater impairment and more rapid deterioration of cardiac function, which may contribute to poor outcomes. Abstract : Access the CME test here and search by article title.